THE APPLICATION OF THE ROLE PLAYING LEARNING MODEL TOWARDS STUDENTS' LEARNING OUTCOMES ON THE MATERIAL OF EATING AND BEING EATEN IN SCIENCE LEARNING IN GRADE V OF SDN LAMTHEUN ACEH BESAR - Fitriani, Desy; Safiah, Intan; Tursinawati, Tursinawati (Universitas Syiah Kuala, 2025)
This study is based on the importance of quality education in improving the quality of learning. One approach that can be applied is the Role Playing learning model, which allows students to learn actively through roles in learning scenarios. This study aims to describe the effectiveness of the application of the Role Playing model on student learning outcomes on food chain material in grade V of SD Negeri Lamtheun, Aceh Besar. This study uses a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation to obtain an overview of students' experiences and responses in learning using the Role Playing model. The results showed that the application of this model increased students' understanding of the concept of the food chain, encouraged active participation, and improved their communication skills. In addition, the learning atmosphere becomes more interesting and enjoyable, so that students can more easily understand the material concretely. Based on the results of the study, the Role Playing model has proven effective in improving student learning outcomes. Therefore, this model is recommended to be applied in science learning to create a more active, creative, and meaningful learning environment.